ENHANCING EFFENCICY OF THE CHALLENGE METHOD IN TEACHING ENGLISH - Parmankulova , D.R.; Kizdarbekova, M.A. (Educational Research in Universal Sciences, 2023)
The article provides a literary review of effective methods used in teaching English. Today, English is the main tool for access to world- class opportunities. The purpose of the article is to study the features and effectiveness of modern methods in accordance with modern requirements. To identify effective methods for the development of cognitive processes in the training of students. Challenge method is the development of independent decision-making skills, the formation of different - communicative skills in group or individual work in language learning. The effectiveness of the use of the Challenge method in teaching English is described. Using the Challenge method, students become accustomed to finding solutions to problems and implementing them, identifying topics that are difficult for students to learn. Once the problem is identified, students formulate questions, the answers of which bring them closer to solving the problem. The guiding questions identified by the learners help to determine what knowledge is needed to solve the problem and to map the knowledge. Students determine what lessons, lectures, resources are needed to solve the problem. This method considers the effective teaching of English. Students learn the language in accordance with social and communicative skills, while the main focus in the acquisition of language is a thorough and intensive learning.